Clinical characteristics and outcomes of infection with human T-lymphotropic virus in a non-endemic area: a single institution study - Gang, Margery; Gao, Feng; Poondru, Sneha; Thomas, Theodore; Ratner, Lee (Frontiers in Microbiology, 2023)
Introduction Our understanding of human T-cell lymphotropic virus (HTLV) remains largely based on epidemiologic and clinical data from endemic areas. Globalization has resulted in migration of HTLV carriers from endemic to non-endemic areas, and a rise of HTLV infection in the United States. Yet, due to the historical rarity of this disease, affected patients are often under- and mis-diagnosed. Thus, we sought to characterize the epidemiology, clinical features, comorbidities, and survival of HTLV-1- or HTLV-2-positive individuals identified in a non-endemic area. Methods Our study was a single institution, retrospective case-control analysis of HTLV-1 or HTLV-2 patients between 1998 and 2020. We utilized two HTLV-negative controls, matched for age, sex, and race, for each HTLV-positive case. Hematologic, neurologic, and rheumatologic covariates were evaluated as variables affecting overall survival (OS). Results We identified 38 cases of HTLV infection, of whom 23 were HTLV-1 and 15 were HTLV-2 positive. The majority (~54%) of patients in our control group received HTLV testing for transplant evaluation testing, compared to ~24% of HTLV-seropositive patients. Co-morbidities associated with HTLV, hepatitis C seropositivity were higher in HTLV-seropositive patients compared to controls (OR 10.7, 95% CI = 3.2 – 59.0, p < 0.001). Hepatitis C and HTLV co-infection resulted in decreased OS, compared to no infection, hepatitis C infection alone, or HTLV infection alone. Similarly, patients with any cancer diagnosis and HTLV infection had worse OS compared to patients with cancer or HTLV alone. HTLV-1 positive patients had lower median OS compared to HTLV-2 patients (47.7 months vs. 77.4 months). In univariate analysis, the hazard for 1-year all-cause mortality was increased among patients with HTLV-seropositivity, adult T-cell leukemia, acute myelogenous leukemia, and hepatitis C infection. When corrected, multivariate analysis showed that HTLV seropositivity was no longer associated with 1-year all-cause mortality; however association with AML and hepatitis C infection remained significant. Conclusion HTLV-seropositivity was not associated with increased 1-year mortality in multivariate analysis. However, our study is limited by our small patient sample size, as well as the biased patient control population due to selection factors for HTLV testing.